2021
DOI: 10.18280/mmep.080607
|View full text |Cite
|
Sign up to set email alerts
|

CFD-FEM Modeling of a Floating Foundation under Extreme Hydrodynamic Forces Generated by Low Sea States

Abstract: The high development of the offshore industry for supporting new marine and renewable energy projects requires a constant improvement of methods for structure designing. Because recent studies warned that maximum environmental loads occur during low sea states and not during extreme sea states as recommend by the offshore standards (e.g., RP 2AWSD-2014), this study used measured wave and current data for analyzing that warning. The Colombian Caribbean coast was selected as the study area, and in situ ADCP data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…ANSYS is a Multiphysics model able to simulate complex fluid-structure interactions and other physical problems. In Table 1 are listed the used boundary conditions, as well as the fluid control volume properties and the applied numerical methods recommended in Rueda-Bayona et al [41]. The used spatial discretization, solution methods and turbelence parameters for the CFD modelling (Table 1) were tuned considering the convergence of the numerical solution and the expected behavior of a perturbed hydrodynamic field [42,43].…”
Section: Endmentioning
confidence: 99%
“…ANSYS is a Multiphysics model able to simulate complex fluid-structure interactions and other physical problems. In Table 1 are listed the used boundary conditions, as well as the fluid control volume properties and the applied numerical methods recommended in Rueda-Bayona et al [41]. The used spatial discretization, solution methods and turbelence parameters for the CFD modelling (Table 1) were tuned considering the convergence of the numerical solution and the expected behavior of a perturbed hydrodynamic field [42,43].…”
Section: Endmentioning
confidence: 99%
“…The plant floating bed system, a deformation of the artificial wetland system, is a promising solution that can effectively remove pollutants from sewage and promote the resourceful utilization of sewage while combining sewage treatment and utilization. Ecological floating bed system is a common technology for purifying water quality and reducing water pollutants, featuring low cost, wide applicability and convenient management and maintenance [1][2][3][4][5]. García-Ávila et al [6] used reeds and balsam fir as wetland plants and the results of their experiments showed that balsam fir had a high capacity to remove pollutants such as biochemical oxygen demand (80.69%), chemical oxygen demand (69.87%), ammoniacal nitrogen (69.69%), total phosphorus (50%), total coliforms (98.08%) and faecal coliforms (95.61%).…”
Section: Introductionmentioning
confidence: 99%
“…Wave power and marine current energy depend on the interaction of winds, waves, and sea currents, where the energy conversion from kinetic potential depends on the water depth and sea state transitions [8]. Low sea states are characterized by significantly reduced wave heights (Hs < 1 m), which are frequently not considered for offshore structure design despite it being proven that low sea states generate significant transient current accelerations that can affect the structural health of marine technologies [9,10].…”
Section: Introductionmentioning
confidence: 99%